PENGARUH KONSERVATISME AKUNTANSI, PROFITABILITAS, DAN LEVERAGE TERHADAP EARNINGS RESPONSE COEFFICIENT DENGAN VARIABEL MODERATING UKURAN PERUSAHAAN - Ardiyani, Dewi; Zulaika, Tatik; Y. Asi, Oktobria; Joni Pambelum, Yohanes (Universitas Sarjanawiyata Tamansiswa, 2024)
Profits are an important part of the information used by investors to measure the impact of profits on stock returns. Earnings Response Coefficient is profits are an important part of the information used by investors, to measure the impact of profits on stock returns, the earnings response coefficient is one of the tools to measure earnings quality. The purpose of this research is determine the effect of accounting conservatism, profitability, and leverage on earnings response coefficient with firm size as moderating variable on influence of accounting conservatism, profitability, and leverage on earnings response coefficient. This study used 38 is sub sector food and beverages manufacturing companies listed Indonesia Stok Exchange (IDX) in 2018-2021 with sampling technique used in this research was purpose sampling. The method of data analysis used is moderate regressiom analysis (MRA). The result of this study indicate accounting conservatism and profitability have positive effect on earnings response coefficient and leverage have negative effect on earnings response coefficient. Firm size is able to moderate on influence of accounting conservatism, profitabilty, and leverage on earnings response coefficient.